The Edinburgh companion to twentieth-century British and American war literature - Piette, Adam; Rawlinson, Mark (Ebook Central Academic Complete Collection, 2012)
The first reference to literary and cultural representations of war in 20th-century English & US literature and film. Coving the two World Wars, the Spanish Civil War, the Cold War, the Vietnam War, the Troubles in Northern Ireland and the War on Terror, this Companion reveals the influence of modern wars on the imagination. These newly researched and innovative essays connect 'high' literary studies to the engagement of film and theatre with warfare, extensively cover the literary and cultural evaluation of the technologies of war and open the literary field to genre fiction. Divided into 5 sections:. 20th-Century Wars and Their Literatures Bodies, Behaviours, Cultures The Cultural Impact of the Technologies of Modern War The Spaces of Modern War Genres of War Culture Key Features. All-new original essays commissioned from major critics and cultural historians Reflects the way war studies are currently being taught and researched: in the volume's approach, structure and breadth of coverage For scholars: core arguments and detailed research topics For students: Historically grounded topic- and genre-based essays, useful forstudying the modern period and war modules